Comparative microRNA Transcriptomes in Domestic Goats Reveal Acclimatization to High Altitude - Feng, Siyuan; Ma, Jideng; Long, Keren; Zhang, Jinwei; Qiu, Wanling; Li, Yan; Jin, Long; Wang, Xun; Jiang, Anan; Liu, Lingyan; Xiao, Weihang; Li, Xuewei; et al. (Frontiers in Genetics, 2020)
High-altitude acclimatization is a representative example of vertebrates’ acclimatization to harsh and extreme environments. Previous studies reported sufficient evidence for a molecular genetic basis of high-altitude acclimatization, and genomic patterns of genetic variation among populations and species have been widely elucidated in recent years. However, understanding of the miRNA role in high-altitude acclimatization have lagged behind, especially in non-model species. To investigate miRNA expression alterations of goats that were induced by high-altitude stress, we performed comparative miRNA transcriptome analysis on six hypoxia-sensitive tissues (heart, kidney, liver, lung, skeletal muscle, and spleen) in two goat populations from distinct altitudes (600 m and 3000 m). We obtained the expression value of 1391 mature miRNAs and identified 138 differentially expressed (DE) miRNAs between high and low altitudes. Combined with tissue specificity analysis, we illustrated alterations of expression levels among altitudes and tissues, and found that there were coexisting tissue-specific and -conserved mechanisms for hypoxia acclimatization. Notably, the interplay between DE miRNA and DE target genes strongly indicated post-transcriptional regulation in the HIF-1, insulin, and p53 signaling pathways, which might play significant roles in high-altitude acclimatization in domestic goats. It's also worth noting that we experimentally confirmed miR-106a-5p to have a negative regulation effect on angiogenesis by directly targeting FLT-1. These results provide insight into the complicated miRNA expression patterns and regulatory mechanisms of high-altitude acclimatization in domestic goats.